The Problem of Combating Organized Crime in the Penal System of Republic of Kazakhstan and other Countries - KAINAR, Erbolat E. (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
In this paper the author studies the problems of organized crime and its manifestations in correctional facilities of the penal system. Today, there are no concrete ways and methods to combat organized crime and its manifestations in the correctional system. Organized crime groups in correctional facilities are combated only by operational staff of those facilities. Meantime, the results of operational staff’s work are not efficient enough. As distinct from other criminal groups, organized crime groups in correctional facilities of the penal system have their features in the criminal world, specific skills in their own criminal groups, own notions of criminal organizations and culture, own laws and individual criminal skills of each group member. Crime growth in the correctional system fell on the peak of organized crime combating in the USSR in 1930’s when crime gangs, strengthening due to collectivization and famine, began getting into more organized groups. The basic uniting force in the criminal world was the trend to non-political antagonism and contumacy, while code-bound thieves in law became its elite, calling themselves the keepers of criminal tradition of the tsarist Russia. In the course of writing this paper the author made comparative analysis of scientific achievements in combating organized crime in the penal systems of the CIS and foreign countries. While working on this paper the author visited correctional facilities of a number of Kazakhstan regions, spoke with convicted persons following members of organized crime groups, found out the opinions of correctional facilities’ staff from various departments on that matter and analyzed them. As a result of the works carried out, the author came to the following conclusions: the problem of organized crime combating and liquidation of its manifestations in the penal system of Kazakhstan Republic still remains open. The problem of organized crime combating in Kazakhstan Republic’ penal system is similar to that in the penal systems of all former Soviet Union states. Their similarity is accounted for the established punishment system under the codes of thieves in law, organized crime groups inside the penal system. It may be surely stated that only as a result of concrete combating organized crime in correctional facilities of the penal system and full liquidation of any manifestation of codes of thieves in law, other problems of the penal system may be solved. For instance, matters of rehabilitation of convicted persons, decrease of relapse into crime, easement of the conditions of convicted persons’ social adaptation, equality of rights of convicted persons, etc. may be solved.
Keywords: Organized crime, criminal groups, non-cooperating convicted persons, administration staff, correctional facilities, criminal world, criminal shared fund, thieves in law, codes, criminal bosses, prison enforcer